2015
DOI: 10.1111/jon.12282
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelioidosis: Craniospinal MRI Findings in Burkholderia pseudomallei Infection

Abstract: Spread of microabscesses along white matter tracts and frequent trigeminal nerve involvement are unique imaging characteristics of CNS melioidosis. These findings may provide insight into potential mechanisms for B. pseuodomallei entry into the CNS through direct axonal transport in cranial nerves bypassing the blood brain barrier. Prompt recognition of the neuroimaging features of this potentially fatal infection may allow for early microbiological culture and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…In patients with CNS involvement, CT images may be normal and magnetic resonance imaging (MRI) is preferred. MRI often shows extensive hyperintense changes on T2-weighted images; microabscesses, leptomeningeal enhancement, and trigeminal nerve involvement are also common [ 54 , 80 , 81 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In patients with CNS involvement, CT images may be normal and magnetic resonance imaging (MRI) is preferred. MRI often shows extensive hyperintense changes on T2-weighted images; microabscesses, leptomeningeal enhancement, and trigeminal nerve involvement are also common [ 54 , 80 , 81 ].…”
Section: Diagnosismentioning
confidence: 99%
“…A recent study by Chia-Tsong Hsu et al. 8 observed rim-enhancing microabscesses in the brain parenchyma and medulla of the spinal cord, particularly along white matter tracts; in addition, meningeal enhancement, extradural and scalp abscesses and skull osteomyelitis were also found. Ring-enhancing lesions and spinal extradural collections were also reported by Deuble et al., 7 while abscess formation and collections were demonstrated by Muthusamy et al.…”
Section: Discussionmentioning
confidence: 93%
“… 5 , 7 , 8 The most recent study was a retrospective analysis of the magnetic resonance imaging findings in 10 patients with neuromelioidosis. 8 The main features were the presence of rim-enhancing microabscesses along white matter tracts (including the corticospinal tracts, corpus callosum and cerebellar peduncles), thickening and enhancement of the trigeminal nerves (with spread to the trigeminal nuclei) and extra-axial disease (meningeal enhancement, extradural abscess, skull osteomyelitis and/or scalp abscess). 8 In the present study, disease characteristics and imaging features were analyzed retrospectively in patients with neuromelioidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these nerves provide direct conduits between the nasal cavity and the CNS. [13]We have previously shown that B. pseudomallei rapidly (within 24 h of intranasal inoculation) reached the olfactory bulb via the olfactory nerve, or the brainstem and spinal cord via the trigeminal nerve in mice [14-18]. One study identified thickening of the trigeminal nerve in three out of seven human neurological melioidosis patients, indicative of nerve invasion to the CNS, bypassing the blood-brain barrier.…”
mentioning
confidence: 99%
“…One study identified thickening of the trigeminal nerve in three out of seven human neurological melioidosis patients, indicative of nerve invasion to the CNS, bypassing the blood-brain barrier. The same three patients were also exhibiting signs of sinusitis [13]. We have also shown that the bacterial protein Burkholderia intracellular motility A (BimA), which mimics a eukaryotic actin polymerase to mobilise a tail of host cell actin leading to bacterial motility, cell-cell dissemination and cell-cell fusion, is important for CNS invasion [18].…”
mentioning
confidence: 99%